ANALYSIS OF SUSTAINABLE TOURISM DEVELOPMENT IN THE LAKE TOBA GEOPARK AREA - Sri Rahayu; Megasari Gusandra Saragih (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
The Lake Toba Geopark holds a lot of potential for natural beauty, unique flora and fauna as well as captivating cultural diversity. However, a mature strategy is needed to make the Lake Toba Geopark global. This is because the competition in the tourism sector is very tight. Many other countries also have natural beauty that is not inferior to the Lake Toba Geopark. Therefore, sustainable tourism development is needed for the Lake Toba Geopark so that the Lake Toba Geopark can still be enjoyed by future generations